Africa Unbound: Decolonial Pathways to Sovereignty and Liberation - Ouma, Stephen Onyango (Africana Philosophy, 2026)
This book redefines the debate on Africa's future by confronting the hidden continuities of colonial power that persist in economics, education, and governance. By revealing how structural dependency and epistemic subjugation still constrain the continent's autonomy, this book advocates for a radical reorientation toward self-determination grounded in African values, knowledge systems, and collective agency. The author engages both historical depth and contemporary urgency, offering a visionary blueprint for rebuilding Africa through decolonial thought, ethical leadership, and continental solidarity. Scholarly, provocative, and transformative, the book positions Africa not as a subject of history, but as its author.